2011
DOI: 10.1038/ni.2017
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12 secretion by bone marrow stromal cells is dependent on cell contact and mediated by connexin-43 and connexin-45 gap junctions

Abstract: The chemokine CXCL12 is essential for the function of hematopoietic stem and progenitor cells. Here we report that secretion of functional CXCL12 from human bone marrow stromal cells (BMSCs) was a cell contact-dependent event mediated by connexin-43 (Cx43) and Cx45 gap junctions. Inhibition of connexin gap junctions impaired the secretion of CXCL12 and homing of leukocytes to mouse bone marrow. Purified human CD34(+) progenitor cells did not adhere to noncontacting BMSCs, which led to a much smaller pool of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
121
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(126 citation statements)
references
References 50 publications
5
121
0
Order By: Relevance
“…Second, it has been shown that Cx43 mediates BM stromal cell adhesion to HSCs (29). To address whether the contact of HSCs with BM stromal cells was causal in the control of HSC ROS levels, we cocultured HSC/P cells derived from WT or H-Cx43-deficient mice with preplated FBMD-1 stromal cells, a wellrecognized model of heterocellular hematopoiesis-supporting stroma (30) composed of ROS high and ROS low cell populations (Fig.…”
Section: To Clarify Whethermentioning
confidence: 99%
“…Second, it has been shown that Cx43 mediates BM stromal cell adhesion to HSCs (29). To address whether the contact of HSCs with BM stromal cells was causal in the control of HSC ROS levels, we cocultured HSC/P cells derived from WT or H-Cx43-deficient mice with preplated FBMD-1 stromal cells, a wellrecognized model of heterocellular hematopoiesis-supporting stroma (30) composed of ROS high and ROS low cell populations (Fig.…”
Section: To Clarify Whethermentioning
confidence: 99%
“…Indeed, it was reported in various cell types that the absence of Cx43 leads to a differential cellular transcriptome, which ultimately determines phenotyp- ical changes in cell morphology and cell adhesion suggesting that Cx43 has a direct role on gene transcription (6). On the other hand, studies carried out in osteosarcoma cell lines and in mouse bone marrow stromal cells (BMSCs), have shown that defects in GJIC may alter the subcellular localization and the recruitment of transcription factors to the promoter region of certain genes, impacting upon gene transcription (52,53). In this case, it was hypothesized that differential GJ-mediated passage of second messengers modulates signaling pathways that will affect the binding affinity and/or activity of the transcription factor Sp1.…”
Section: Table III Interaction Of Cx43 With Hnrnps Varies In Ischemiamentioning
confidence: 99%
“…Indeed, the gap junction protein connexin-43 has been shown to regulate HSPC homing and engraftment. While one study has shown that BM stromal CXCL12 secretion requires electromechanical coupling by connexin-43 and -45, 24 another study has shown that connexin-43 deficiency increases BM stromal CXCL12 secretion but it compromises HSC homing and hematopoietic recovery upon myeloablation. 25 This is at least partly due to connexin-43-mediated transfer of high, damaging amounts of reactive oxygen species to the BM stroma, which would protect HSCs during stress hematopoiesis.…”
Section: Autonomic Regulation Of Hematopoiesis and Cancermentioning
confidence: 99%